Penerapan Pendekatan Learning By Doing Dalam Meningkatkan Rasa Kepercayaan Diri Siswa Sekolah Dasar Negeri 3 Tangkiling - Norvia, Lia; Muslimah; Surawan (STIT Muhammadiyah Paciran Lamongan, 2022)
This study aims to determine: (1) How to apply the learning by doing approach in increasing students' self-confidence. (2) The level of student confidence when the learning by doing approach is applied. The method in this research is using mixed methods with a sample of 8 fifth grade students at SDN 3 Tangkiling who are Muslim. Monogenean data collection techniques are observations, questionnaires and interviews with data analysis using the product moment correlation formula. The results of the study show that: (1) The average application of the learning by doing approach in increasing students' self-confidence is 4.15 which is included in the high category so that the learning by doing approach is applied well. (2) The level of student confidence when the learning by doing approach is applied is 97.6% which is categorized as high.